Three-Compartment Model of CAR T-cell Immunotherapy - Rodrigues, Brendon J; Luciana Rodrigues Carvalho Barros; Almeida, Regina Celia (bioRxiv, 2020)
Immunotherapy has gained great momentum with CAR T (chimeric antigen receptor) cellular therapy, in which the patients T lymphocytes are genetically manipulated to recognize tumor-specific antigens to increase elimination efficiency. Although recently approved by FDA to treat B cell malignancies, issues such as dose, administration protocol, toxicity, resistance to immunotherapy, among others, remain open and are the subject of intense research nowadays. Improved CAR T cell immunotherapy requires a better understanding of the interplay between CAR T cell doses and tumor burden. We developed a three-compartment mathematical model to describe tumor response to CAR T cell immunotherapy in immunodeficient mouse models (NSG and SCID/beige) based on two published articles from literature. We modeled different receptors as CART 19BBz or CART 123, and also different tumor targets as HDML-2 and RAJI. We considered interactions between tumor cells, effector T cells, and T cell differentiation into memory T cells; tumor-induced immunosuppressive effects, conversion of memory T cells into effector T cells in the presence of tumor cells, and individual specificities considered as uncertainties in the parameters of the model. The model was able to represent the two considered immunotherapy scenarios. For the HDML-2 scenario, the tumor is eliminated after the immunotherapy with the CAR T cells even in case of a challenge due to the memory T cells long-term immune protection. For the Raji tumor, expressing indoleamine 2,3-dioxygenase (IDO) activity, the model represented tumor dynamics even when IDO inhibitors are introduced. Using in silico studies considering different dosing quantities and tumor burden, we showed that the proposed model is capable of representing the three possible outcomes: tumor elimination, equilibrium, and escape. We found that therapy effectiveness may also depend on small variations in the parameters' values, regarded as intrinsic individual specificities, as T cell proliferation capacity, as well as immunosuppressive tumor microenvironment factors. These issues may significantly reduce the chance of tumor elimination. In this way, the developed model provides potential use for assessing different CAR T cell protocols and associated efficacy without further in vivo experiments. Competing Interest Statement The authors have declared no competing interest. Footnotes * Revised manuscript and new Supplementary data.